The Development of model to import raw material for clothes under management based on theory logistics and supply chain: case study of ABC (Thailand) co, ltd. - Nawattanaprasert, Kritchakhris (Advances in Social Sciences Research Journal, 2019)
The objective of research : 1.To study the issue and form of importing raw materials clothes by management based on the theory of logistics and supply chain case study of ABC (Thailand) Co., Ltd. 2.To create an appropriate format in the import of raw materials by sea. And 3.To increase the performance related to the operational model to import raw materials clothing by sea re-constructed. As well as the cost of transport to import raw materials from overseas by boat with the highest effectiveness and efficiency. The research results reveal the process development follow by management based on theory logistics and supply chain, could authentically reduce the cost through the application of logistics and supply chain approach; transportation cost, defective or failure cost, and lost and damage cost. Those will directly affect the production and delivery processes, and can create competitive edge in the market; however, one disadvantage is the higher labor cost. Therefore, this is Thailand’s opportunity in terms of presenting potential on lingerie export business to the world market. As a result, the business could bring currency into the country which could give a good answer for this research.